Self-Reported High-Cholesterol Prevalence in the Brazilian Population: Analysis of the 2013 National Health Survey - Lotufo,Paulo A. (2017)
Abstract Background: Data on the prevalence of dyslipidemia in Brazil are scarce, with surveys available only for some towns. Objective: To evaluate the prevalence of the self-reported medical diagnosis of high cholesterol in the Brazilian adult population by use of the 2013 National Health Survey data. Methods: Descriptive study assessing the 2013 National Health Survey data, a household-based epidemiological survey with a nationally representative sample and self-reported information. The sample consisted of 60,202 individuals who reported a medical diagnosis of dyslipidemia. The point prevalence and 95% confidence interval (95%CI) for the medical diagnosis of high cholesterol/triglyceride by gender, age, race/ethnicity, geographic region and educational level were calculated. Adjusted odds ratio was calculated. Results: Of the 60,202 participants, 14.3% (95%CI=13.7-14.8) never had their cholesterol or triglyceride levels tested, but a higher frequency of women, white individuals, elderly and those with higher educational level had their cholesterol levels tested within the last year. The prevalence of the medical diagnosis of high cholesterol was 12.5% (9.7% in men and 15.1% in women), and women had 60% higher probability of a diagnosis of high cholesterol than men. The frequency of the medical diagnosis of high cholesterol increased up to the age of 59 years, being higher in white individuals or those of Asian heritage, in those with higher educational level and in residents of the Southern and Southeastern regions. Conclusion: The importance of dyslipidemia awareness in the present Brazilian epidemiological context must be emphasized to guide actions to control and prevent coronary heart disease, the leading cause of death in Brazil and worldwide.